The measurement of lumbar spinal curvature in Thai population: Relationship to age, gender, and body mass index - Wisuchana Maicami (2018)
Back pain can seriously affect all age groups. There are many factors for causing the changing backbone of the people. However, at present there are still studies quite a few changes in the lumbar spine. Therefore, all data are obtained from Lerdsin hospital. The purpose of this study is to investigate the relationship between age, gender and body mass index of the patients are admitted because of back pain using method for measuring the angulation of the bone with Cobb's Angle method. X-Ray images of the patient's Lerdsin hospital are 493 of people aged between 20-88 years which they can be divided into four groups: 1) 20-29 years, 2) 30-39 years, 3) 40-49 years and 4) over 50 years. The calculations of mean and standard deviation are compared with the relationship between age, gender and body mass index (BMI) affecting the curvature of the lumbar spine. The results show that the first, second, third and fourth groups are approximately at 26.39 ± 12.02 degrees (64 people), 25.78 ± 12.16 degrees (85 people), 26.99 ± 12.79 degrees (106 people) and 25.53 ± 12.96 degrees (243 people), respectively. For the third group, the curvature of the bone is highest all of the age groups, and females are higher than males. It is found that the angle of curvature of the lumbar spine by age are analyzed by One-way ANOVA (p>0.05). The results of the age do not affect the curvature of the lumbar spine and they show patients with underweight and overweight patients. It makes effects of the curvature of the spine that females are more than males. Experts estimate a basis for evaluating underlying disorder patients to receive treatment for back pain that is in the level of risk. © 2014 IEEE.